Increasing Nursing Efficiency Through the Use of Wearable Devices in Patient Management - Catur Budi Susilo; Josefa Flores; Catherine Li (Yayasan Adra Karima Hubbi, 2025)
The healthcare sector faces increasing pressure to improve efficiency in patient management due to rising demands for services and limited nursing resources. The integration of wearable devices in healthcare offers a promising solution to enhance nursing efficiency by providing real-time monitoring and data collection. This study aims to explore the impact of wearable devices on nursing efficiency, particularly in the management of patients with chronic conditions. A mixed-methods approach was employed, combining quantitative analysis of patient outcomes and qualitative interviews with healthcare professionals using wearable technology in clinical settings. The results show that the use of wearable devices led to a 20% reduction in nurse workload, as real-time monitoring allowed for early detection of health issues, reducing the need for frequent in-person checks. Additionally, patient satisfaction increased by 15% due to the continuous monitoring and prompt intervention facilitated by wearable devices. The study concludes that wearable devices can significantly enhance nursing efficiency and improve patient outcomes, particularly in chronic disease management. The integration of these devices into healthcare systems has the potential to alleviate nursing shortages, improve patient care, and optimize resource allocation. However, challenges such as data security and device integration must be addressed for widespread adoption.